Comparative microRNA signatures based on liquid biopsy to identify lymph node metastasis in T1 colorectal cancer patients undergoing upfront surgery or endoscopic resection - Kazuaki Okamoto; Hiroaki Nozawa; Tsuyoshi Ozawa; Yoko Yamamoto; Yuichiro Yokoyama; Shigenobu Emoto; Koji Murono; Kazuhito Sasaki; Mitsuhiro Fujishiro; Soichiro Ishihara (Cell Death Discovery)
Abstract After endoscopic resection of T1 colorectal cancer (CRC) with a high risk of lymph node metastasis (LNM), additional surgery is required. However, the actual frequency of LNM based on conventional risk factors is less than 16%. There is a need for biomarkers to identify T1 CRC carrying a high risk of metastasis to avoid unnecessary radical surgery. Based on the comparison of serum miRNA between stage I/II and stage III from a large-scale in silico dataset, we conducted a validation analysis of the selected miRNAs using plasma samples from LNM-positive and LNM-negative T1 CRC patients who underwent endoscopic treatment followed by radical surgery at our hospital. In the validation cohort, the three-miRNA classifiers (miR-195-5p, miR-221-3p, and miR-193b-3p) effectively identified LNM-positive T1 CRC patients who received upfront surgery with an area under the curve (AUC) value of 0.74. Moreover, in T1 CRC patients after endoscopic resection, miR-195-5p and miR-221-3p were able to predict LNM with an AUC of 0.74. Plasma miRNA signatures may serve as effective predictors for LNM in T1 CRC both before upfront surgery and after endoscopic resection.